Pengolahan Limbah Cair Industri Beauty dan Personal Care Menggunakan Metode Koagulasi dan Flokulasi - Hakim, Rusnia Junita; Adelina, Dina; Ismet, Rhahmasari; Muttaqim, Maulana (Politeknik Negeri Lhokseumawe, 2025)
The beauty and personal care industry generates wastewater that poses a potential threat to the environment if not properly treated. As a small-scale industry, there is a need for an efficient wastewater treatment technology that requires minimal cost and land area. This study aims to analyze the characteristics of wastewater from the industry and evaluate the effectiveness of coagulation and flocculation processes in reducing pollutant levels. The jar test method was employed using varying doses of coagulant (PAC) and flocculant (anionic polymer) at concentrations of 60, 80, and 100 ppm for PAC, and 1–3 ppm for the polymer. Initial test results indicated that the parameters for TDS, TSS, pH, EC, and turbidity did not meet the effluent quality standards set by the Indonesian Ministry of Environment Regulation No. 5 of 2014. The optimum dosage was found to be 80 ppm PAC combined with 3 ppm anionic polymer, which reduced TSS from 1482 mg/L to 83 mg/L and turbidity from 3120 NTU to 20 NTU. The best reduction in EC was achieved with 100 ppm PAC and 3 ppm polymer, lowering EC from 3210 µS/cm to 399 µS/cm. All parameters, except for TDS, complied with the established effluent quality standards.